2013
DOI: 10.5603/cj.2013.0134
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of platelet indices after acute myocardial infarction treated with primary percutaneous coronary intervention

Abstract: Background: Mean platelet volume (MPV) is a strong predictor of impaired angiographic reperfusion and 6-month mortality in ST-elevation myocardial infarction (MI) treated with primary percutaneous coronary intervention (PCI). No data is available for other platelet volume indices: platelet distribution width (PDW) and platelet large cell ratio (P-LCR). The aim was to assess the impact of 3 platelet volume indices on long-term prognosis in patients treated PDW < 16 fL (17.4% vs. 6.3%, p = 0.0012). PDW was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 20 publications
5
86
0
1
Order By: Relevance
“…Lately the introduction of platelet distribution width (PDW) as a predicting factor has been studied extensively in consideration of its greater reliability in comparison to MPV [3]. PDW was reported to have prognostic value in PCI-treated acute MI [4]. No relationship between PDW and the prevalence of coronary artery disease (CAD) was discovered; however, PDW was related to CAD severity in patients with acute coronary syndrome (ACS) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Lately the introduction of platelet distribution width (PDW) as a predicting factor has been studied extensively in consideration of its greater reliability in comparison to MPV [3]. PDW was reported to have prognostic value in PCI-treated acute MI [4]. No relationship between PDW and the prevalence of coronary artery disease (CAD) was discovered; however, PDW was related to CAD severity in patients with acute coronary syndrome (ACS) [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in PLCR shows the presence platelet aggregates, micro erythrocytes and giant platelets. 18 Rechciński T et al in their study found that PDW and PLCR, can serve as useful prognostic factors for long-term mortality in patients after acute MI. PDW was found to be one of the independent risk factors of cardiac mortality, as well as of the occurrence of either death, recurrent MI or need for another revascularization procedure.…”
Section: Introductionmentioning
confidence: 99%
“…PDW was found to be one of the independent risk factors of cardiac mortality, as well as of the occurrence of either death, recurrent MI or need for another revascularization procedure. 18 Thus platelets indices are important simple effortless and cost effective tool that can be used and explored extensively especially in countries such as India for predicting the possibility of impending acute coronary events. Hence present study was undertaken to compare the platelet indices viz, MPV, platelet distribution width (PDW), platelet large cell ratio (PLCR) in UA patients and ST segment elevated myocardial infarction (STEMI) with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of PIs in diagnosis of various diseases was reported. Some researchers showed that PIs may be useful adjunctive inflammatory markers of malignant tumors (15), which could predict the patients with acute myocardial infarction (16) and be used to predict placental abruption (17). Nevertheless, contradictory results are sometimes observed on the clinical studies of PIs in other diseases (18,19).…”
Section: Discussionmentioning
confidence: 99%